Comparative analysis of nutritional quality and functional effects of some functional bakery products from Romanian market - Mariana Eftime; Viorel Petrescu; Mihaela Constandache (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
One solution to improve the nutritional level of the population, especially in disadvantaged areas, is the enrichment and fortifying consumer foods. This study aims at analyzing the possible beneficial effects of bread fortified with various micronutrients that gives product functionality. The aim of research is a comparative analysis of nutritional quality and functional effects of bakery products of three major producers in Romania, respectively SC DobrogeaGrup S.A. Constanta, Smart Food Solutions Company and the VelPitar Group. We could identify thus the most efficient bakery product from the nutritional perspective as well as from the functional one. Thus, Whole Wheat bread is an important source of dietary fiber which can reduce blood cholesterol levels thereby decreasing the risk of heart disease, can promote proper digestion, can regulate blood glucose, thereby preventing type 2 diabetes and can provide a quick sensation of satiety helping to maintain body weight. Sana Bongrana Ultrafibre is rich in fiber and may reduce risk of diabetes It can also lower blood cholesterol levels, being a functional product recommended for health of cerebral, cardiovascular and digestive systems. BenecolDobrogea product is a threefold functional bread that, in addition to the lowering cholesterol effect, has a high content of fiber, which helps regulate bowel movements and at the same time, a low-carbohydrate, which recommends it to the people with diabetes. Sana BongranaBenexia bread has a remarkable nutritional value and its content of Benexia sage seeds brings an important contribution to the body of ω3 and ω6 fatty acids, with beneficial effects on the functioning of the cardiovascular and immune systems.
Keywords: 330; nutritional intervention; functional effects; functional foods; nutritional quality; synthetic indicator of quality